Career Planning in Elite Soccer: The Mediating Role of Self-Efficacy, Career Goals, and Athletic Identity - Monteiro, Ricardo; Monteiro, Diogo; Torregrossa, Miquel; Travassos, Bruno (Frontiers in Psychology, 2021)
This study proposed a model to examine the role of self-efficacy, career goals and athletic identity on career planning of elite soccer players. Two hundred and eighty-one elite soccer players (male) participated in this study. Means, standard deviations and bivariate correlations were calculated for the variables under analysis. The hypothesized effect of self-efficacy, career goals and athletic identity on career planning was tested using structural equation modeling. Results supported the adequacy of the proposed model in explaining the career planning. Career planning is positively influenced by the level of players’ self-efficacy through the definition of career goals and negatively influenced by the level of athletic identity. At the same time players’ self-efficacy through the definition of career goals positively influenced athletic identity. These findings reinforce the important role of self-efficacy and career goals for development of athletic identity and career planning and at the same time the opposite relationship between athletic identity and career planning. Thus, it is suggested that a balance on athletic identity, maintaining high levels of self-efficacy and career goals is required to improve the process of career planning and retirement.